Analisis Potensi Sektor Ekonomi dengan Metode LQ, Shift Share dan Tipologi Klassen di Kota Semarang - Verda Veransiska; Niniek Imaningsih (Universitas Batanghari Jambi, 2022)
The purpose of this research is to determine the existence of a leading sector and to determine the potential of the economic sector and analysis of the leading sector in the city of Semarang. This research uses secondary data for 6 years in the 2015-2020 period. The analytical tools used are LQ analysis, SS, Klassen typology and simple regression using SPSS 13. With the results of LQ analysis, it can be concluded that there are 10 basic sectors. The one who got the highest LQ score was in the construction sector (F) of 2,503. The results of Klassen's Typology analysis obtained information that the city of Semarang was included in quadrant II. Based on the results of simple regression analysis seen from the significance value, it can be concluded that the basic economic sector variable (X1) and the non-basic economic sector (X2) have an effect on the growth variable (Y).